Implementation of Lean Construction as a Solution for the Covid-19 Impacts in Residential Construction Projects in Lima, Peru - Verán-Leigh, Daniel; Brioso, Xavier (Pontificia Universidad Católica del Perú. Facultad de Arte y Diseño, 2021)
At the beginning of 2020, a virus discovered in the province of Wuhan in China identified as SARS- COV-2, denominated COVID-19, began to spread globally, being identified by the World Health Organization (WHO) as a pandemic on March 13 since the epidemic has spread to several countries in all the continents and affects a large number of people (WHO 2020). In Peru the entry of COVID-19 caused the Peruvian government to take different options to control its spread such as mandatory quarantines and lockdowns. In front of this scenario, the Architecture Engineering and Construction (AEC) sector had to reinvent itself since it is a sector where work depends on a significant amount of personnel (IPE 2020). Furthermore, the level of industrialization in Peru is significantly lower compared with industrialized countries, generating that the consumption of labor is greater as well as the cost of the project, searching for new solutions to improve productivity. Moreover, considering the new sanitary measures for COVID-19 including new health protocols, controls, and improvement of working sanitary standards. Therefore, the main purpose of the present paper is to present a planning proposal for a system that integrates the Lean tools and the COVID-19 protocol for armed concrete buildings in Peru and present the preliminary results of its modification on the production system, design of work schedules, planning meetings, among other aspects of the construction system.
Keywords: COVID-19; Lean construction; Last Planner® System; Construction system; https://purl.org/pe-repo/ocde/ford#2.01.01